PENINGKATAN KUALITAS PEMBELAJARAN IPS SD MELALUI PROBLEM BASED LEARNING BERBANTUAN AUGMENTED REALITY - Imaduddin, Muhammad; Andriningrum, Hana; Syauqi Malik, Muh; Febriana Wati, Ika; Ardhyantama, Vit; Indrawati, Delia; Kususma Wardani, Helda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of the study was to improve the quality of elementary school social studies learning through the application of Problem-Based Learning (PBL) assisted by Augmented Reality (AR). The research design was adopted from the Kemmis and Taggart spiral design including the stages of planning, action, observation, and reflection. The subjects involved included fifth-grade students of SDN Sendangmulyo 01 Semarang City who were tested and observed. The data collected were then analyzed qualitatively and quantitatively. The results showed a significant increase in teacher skills, student activities, and learning outcomes. Teacher skills showed a significant increase, with an average score of Cycle 1 of 69.64% (good category), Cycle 2 of 73.21% (good), and Cycle 3 of 87.5% (very good). Student activity also increased, with an average score of Cycle 1 of 67.93% (good), Cycle 2 of 73.70% (good), and Cycle 3 of 81.89% (very good). The classical completeness of student learning outcomes showed a stable increase, from 64.85% in Cycle 1 to 75% in Cycle 2, and 85.71% in Cycle 3. Based on the findings, it can be concluded that the implementation of the AR-assisted PBL model is effective in improving the quality of social studies learning, as evidenced by increased teacher skills, student activities, and learning outcomes.